Metabolic pathways inferred from a bacterial marker gene illuminate ecological changes across South Pacific frontal boundaries - Eric J. Raes (Nature Portfolio, 2021)
Extracting functional information from 16S rRNA data surveys would provide a valuable tool for large-scale functional ecology. Here, the authors use PICRUSt2 to infer metabolic functions from bacterial marker gene data across the South Pacific Ocean, and compare them with rate data, biomass estimators and predictions based on shotgun metagenomes.